Pelaksanaan pelayanan publik terhadap peningkatan kepercayaan masyarakat pada kantor kecamatan simpang mamplam kabupaten bireuen - Maulida Mutia; Muhammad Nasir; Zainal Abidin (Fakultas Hukum Universitas Malikussaleh, 2022)
This study aims to determine the implementation of public services to increase public trust in the Simpang Mamplam District office, Bireuen Regency. One of the government organizations that carry out general government duties is the sub-district government. A sub-district is a government organization formed in a regency/municipal area led by a sub-district head. That the problem in this research is how the implementation of public services to increase public trust and what are the obstacles and efforts made by the employees of the Simpang Mamplam District office, Bireuen Regency. The method used is the empirical juridical method with qualitative analysis, with the research location at the Simpang Mamplam District office, Bireuen Regency. Based on the results of the study, it is known that in the implementation of public services to increase public trust in the Simpang Mamplam District office, Bireuen Regency, the following are: service requirements have been carried out by placing announcements about technical requirements near the service counter; ease in managing and fulfilling service requirements that sub-district employees have provided clarity of information so that it has made it easier for the community to service; clarity of flow in service procedures that sub-district employees have interacted directly with the community related to service flow; service completion time that the community as the recipient of the document has obtained time certainty with the rule of 14 working days; details of the cost of free administration services are not charged any fees.